Physical activity patterns and dietary habits of undergraduate students - EBENEZER ESSAW; MONDAY OMONIYI MOSES; DANIEL AFRIFA; ISAAC KWAKU ACHEAMPONG; WINIFRED MENSAH; LEMUEL OWUSU (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: ‪Data about physical activity report card for Ghanaian children and youth are available but reports on physical activity patterns and dietary habits of undergraduates are scarce. Material and methods: ‪This cross-sectional study sampled 278 participants (161 males, 117 females, mean age = 20.73 ± 1.72 years). Blood pressure, heart rate, physical activity patterns and dietary habits were measured. Results: ‪Most (83.1%) of the sample predominantly engaged in household activities. Time spent on treadmill/ cycling activities is significantly higher in females than males (P = 0.018). Day/week for high intensity sports was higher in males (P = 0.005), while household work was significantly higher in females (P = 0.032). Few people observed breakfast. There was poor consumption of soft drinks, vegetables, fresh fruits, dairy products, fast-foods, fried foods, and cake/biscuit twice/three times a week; 70.3% seldom consumed energy drinks; 49.8% ate the main meal daily. Males significantly had higher systolic blood pressure (SBP) (P = 0.014) and consumed fried foods habitually more often than females (P = 0.026). Conclusions: ‪Participants mainly involved in low physical activities and consumed less than recommended amounts of fruits and vegetables per week. Proactive and regular health-enhancing physical activity interventions would stimulate participation and healthy dietary habits of university students.